Micro Finance and Poverty Alleviation: The Case of Kerala’s Kudumbashree - M.A.Oommen (Asian Journal of PROFESSIONAL ETHICS & MANAGEMENT, 2014)
Micro finance is an emerging reality in contemporary development discourse and has come to occupy a significant place in financial intermediation in India. Kudumbashree of Kerala, a community- based self-help organisation of poor women, although started as a micro-finance agency soon became an active subsystem of local governments and embarked upon several activities that address the question of poverty reduction. This paper attempts to narrate the story of Kerala’s Kudumbashree as a women empowerment and anti-poverty programme, not only for its members but also for the wider community.